A Detailed Study of Hibiscus Rosa Sinesis L: Phytochemistry, Pharmacological Activities Therapeutic Uses and Its Antimicrobial, Antioxidant Activities - Sarwade, Prakash Pralhad; Bongale, Manoj Manjunath; Mittal, Nidhi; Chand, Subhash; Vijayalakshmi, K.; ., Radhika; Khongshei, Rapborlang; (Sarwade), Kavita Narayan Gaisamudre (Asian Journal of Pharmaceutical Research and Development, 2025)
Rosa canina L., which is more commonly known as rosehip, has become a plant of great scientific interest due to its nutritional, cosmetic, and therapeutic applications. This review study highlights the fact that the high levels of vitamins, carotenoids, tocopherol, and phenolic acid in this substance are responsible for its anticarcinogenic, hepatoprotective, antioxidant, and anti-inflammatory properties. The German Commission E published a negative monograph on rose hip, rose hip and seed, and rose hip seed due to insufficient evidence of their effects and usefulness. As a result, a literature review was conducted to outline the pharmacological and clinical effects of Rosa canina L. in order to re-evaluate its usefulness in traditional medicine. Several rose hip and rose hip and seed formulations have been demonstrated to offer antioxidant and anti-inflammatory effects. Such action mechanisms involve lipophilic components. Litozin, a proprietary powder made from rose hips and seeds, has been shown to be beneficial in treating patients with osteoarthritis, rheumatoid arthritis, and low back pain in several exploratory investigations. In addition to vitamin C, a number of the components found in rose hips possess strong antioxidant and radical scavenging activities. The pharmacological and clinical effects that were found can be explained by a number of different components, including as phenolics, terpenoids, galactolipids, carotenoids, fruit acids, and fatty oils. In addition, anti-inflammatory effects include lowering the levels of pro-inflammatory cytokines and chemokines, NF-kB signalling, pro-inflammatory enzymes (COX1/2, 5-LOX, and iNOS), C-reactive protein levels, PMN chemotaxis and chemoluminescence, and pro-inflammatory metalloproteases.